Analisis Pengujian Tahanan Kontak Disconnecting Switch atau PMS Terhadap Rugi Daya Penghantar di Gardu Induk Telukjambe - Theresia Shintauli Novalin (Electro Luceat, 2021)
One of the equipment contained in the Substation is a Disconnecting Switch or Separator (PMS), the equipment functions as an electrical circuit separator switch without a load current. The contact resistance test needs to be carried out to determine the value of the contact resistance and the resistance in the contact because it affects the power loss in the conductor. This research was conducted on Busbars 1 and 2 at the 150 KV Substation Telukjambe. After calculation and analysis, it can be said that the contact resistance value is included in the normal category because the permissible standard value is 100, so repairs do not need to be made. By assuming one month to calculate and analyze power loss, electrical energy loss, the largest power loss occurs in busbar 1 phase R, which is 0.0003 kW and the lowest power loss is on busbar 2 phase S and T, which is 0.00009 kW, loss The largest Electrical Energy occurs in Busbar 1 phase R, which is 0.216 kWh and the lowest Electrical Energy Loss is in Busbar 2 phase S and T, which is 0.0648kWh. The greater the value of Power Loss, the greater the Value of Electrical Energy Loss.